2014
DOI: 10.17129/botsci.98
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity in Alcea (Malvaceae) using SRAP markers

Abstract: Abstract:In this work, sequence-related amplifi ed polymorphism (SRAP) marker was employed to assess the genetic diversity and genetic similarity relationships among14 species of Alcea collected from northwest of Iran. Seventeen SRAP primer combinations generated 104 fragments, of which 97 (93%) were polymorphic, with an average of 5.7 polymorphic fragments per primer. Percentage of polymorphism ranged from 50% (ME2-EM6) to a maximum of 100%, and mean polymorphism information content value obtained was 0.3. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Utilizing RAPD markers, OZTÜRK et al (2009) evaluated the 18 Alcea species' genetic profiles and found a considerable difference (0.13 to 0.69) between them. In the BADRKHANI et al (2014) report, the sequence-related intensified polymorphism (SRAP) marker was used to evaluate the genetic variousness and genetic resemblance links among 14 Alcea species gathered from northwest Iran. Seventeen SRAP primer mixtures yielded 104 pieces, with a norm of 5.7 polymorphic pieces for each primer (93%) and 97 (93%) polymorphic fragments.…”
Section: Species Identification and Genetic Diversitymentioning
confidence: 99%
“…Utilizing RAPD markers, OZTÜRK et al (2009) evaluated the 18 Alcea species' genetic profiles and found a considerable difference (0.13 to 0.69) between them. In the BADRKHANI et al (2014) report, the sequence-related intensified polymorphism (SRAP) marker was used to evaluate the genetic variousness and genetic resemblance links among 14 Alcea species gathered from northwest Iran. Seventeen SRAP primer mixtures yielded 104 pieces, with a norm of 5.7 polymorphic pieces for each primer (93%) and 97 (93%) polymorphic fragments.…”
Section: Species Identification and Genetic Diversitymentioning
confidence: 99%